APOSTO: DA PERSPECTIVA NORMATIVISTA À PERSPECTIVA FUNCIONALISTA (PERcursos Linguísticos, 2025)
Abstract: From the point of view of normative grammars and from the syntactic point of view, the apposition is considered an accessory term of the sentence (CEGALLA, 2005; CUNHA; CINTRA, 2007), a perspective that finds an echo in textbooks (TESOTO; DISCINI, 1994; TERRA; CAVALLETE, 2002; SARMENTO, 2009; OLIVEIRA, 2012). It is, therefore, a term that can be removed without prejudice to the structure of the sentence. From a functional-communicative point of view, the apposition plays an important syntactic-pragmatic role, contributing to the degree of informativeness in the multipropositional discourse (GIVÓN, 1984; 1995; 2001). The objective of this work is to analyze the syntactic function in the discourse, the product of the communicative act. To this end, a qualitative approach is offered with fifteen news titles, taken from online newspaper sites, about the dog Wilson, involved in the rescue of children missing after a plane crash in Colombia on the first day of May 2015. Results show that the explanatory apposition demands a greater degree of informativeness and, therefore, a greater linguistic coding, precisely because it needs to retrieve information in the memory of the potential newspaper reader, due to the fact that it is a genre linked to digital platforms and the speed with which information and other content is disclosed.